Les défis et mirages de la recherche intervention sur les temps de travail - Madeleine Bourdouxhe; Georges Toulouse; Yvon Quéinnec (Perspectives Interdisciplinaires sur le Travail et la Santé)
As free trade and market globalization increase corporate competition and the need for flexible work organization, there is a growing demand for research on the health and safety impacts of new types of work schedules, such as rotating 12-hour shifts. The paper describes two cases of action research in companies in which work schedule problems turned out not to be the most pressing concern. Furthermore, the workplace partners appeared uninterested in analyzing work and task requirements or evaluating current staffing levels prior to designing or evaluating new work schedules. This led the researchers to reflect upon the value of their interventions and the meaning of occupational health itself.